Dampak Kurangnya Pelatihan Terhadap Efektivitas Penerapan Kurikulum Merdeka Di SDN Belitung Selatan 7 - Ani Yulianti; Mudah Mudah; Riska As Sevilla; Zulfa Huriah Dina Kazimah; Aslamiah Aslamiah; Diani Ayu Pratiwi (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study aims to evaluate the effect of lack of training on the success of the implementation of the Independent Curriculum at SDN Belitung Selatan 7. The Independent Curriculum is an educational policy that provides flexibility in the learning process, allowing teachers to adjust the material to the needs of students. The Independent Curriculum emphasizes flexibility in learning, but its implementation requires a deep understanding from educators. Lack of training for teachers can hinder the optimal implementation of this curriculum, which has an impact on the lack of innovation in teaching methods, difficulty in adjusting the material to the needs of students, and the low effectiveness of the teaching and learning process. This study used a qualitative approach involving teacher interviews and observations. The results showed that teachers who lack adequate training tend to have difficulty in compiling teaching modules or teachers are less prepared in teaching the current independent curriculum that is appropriate and applies a student-centered learning approach. Therefore, continuous training is very important to improve teachers' ability to implement the Independent Curriculum properly and achieve optimal educational outcomes at SDN Belitung Selatan 7.